1996
DOI: 10.1074/jbc.271.46.28868
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylglucosaminyl Transferase Regulates the Expression of the Sulfoglucuronyl Glycolipids in Specific Cell Types in Cerebellum during Development

Abstract: In the adult cerebellum, sulfoglucuronyl glycolipids (SGGLs) are specifically localized in Purkinje cells and their dendrites in the molecular layer. Other major cell types such as granule neurons and glial cells lack SGGLs. To explain the cell specific localization and the known biphasic expression of SGGLs, enzymic activities of four glycosyltransferases involved in the biosynthesis of SGGLs were studied in murine cerebellar mutants, in distinct cellular layers of rat cerebellum, and in isolated granule neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…4) The expression level of the ␤3Gn-T5 transcript in various cultured cancer cells was well correlated with the Lc 3 Cer synthesizing activity. 5) The changes in the ␤3Gn-T5 transcript level during HL-60 differentiation and during rat brain development were consistent with those of the Lc 3 Cer synthesizing activity as reported by others (15,20,35,46).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…4) The expression level of the ␤3Gn-T5 transcript in various cultured cancer cells was well correlated with the Lc 3 Cer synthesizing activity. 5) The changes in the ␤3Gn-T5 transcript level during HL-60 differentiation and during rat brain development were consistent with those of the Lc 3 Cer synthesizing activity as reported by others (15,20,35,46).…”
Section: Discussionsupporting
confidence: 88%
“…In particular, the expression level of two SGGLs, SGGL-1 and SGGL-2, carrying the HNK-1 epitope is determined by the Lc 3 Cer synthase (15, 19 -22, 46). The change in the level of ␤3Gn-T5 transcript in developing rat brain almost paralleled that in Lc 3 Cer synthesizing activity reported previously (15,20,46). This strongly indicated that ␤3Gn-T5 is the Lc 3 Cer synthase.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In adult cerebellum, it is restricted to Purkinje cells (8). The biological function of this molecular diversity is unclear, but the vital role of glycosphingolipids has been demonstrated by the fact that their complete deficiency in mice leads to early embryonic lethality (see below).…”
mentioning
confidence: 99%